2019
DOI: 10.1002/jbmr.3889
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bortezomib to Bone Increases Its Bone Anabolic Activity and Reduces Systemic Adverse Effects in Mice

Abstract: Bortezomib (Btz) is a proteasome inhibitor approved by the FDA to treat multiple myeloma. It also increases bone volume by promoting osteoblast differentiation and inhibiting osteoclastogenesis in mice. However, Btz has severe systemic adverse effects, which would limit its use as a bone anabolic agent. Here, we designed and synthesized a bone-targeted form of Btz by conjugating it to a bisphosphonate (BP) with no antiresorptive activity. We report that BP-Btz inhibited osteoclast formation and bone resorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…BP‐Btz more effectively reduced tumour burden and bone loss than Btz in the 5TGM1 mouse model of MM (Wang, Xiao et al, 2018). In particular, we also demonstrated that BP‐Btz generated significantly less systemic adverse effects, such as thrombocytopenia (Wang, Xiao, et al, 2018) and peripheral neuropathy (Wang et al, 2020), compared with Btz alone.…”
Section: Multiple Myelomasupporting
confidence: 54%
See 1 more Smart Citation
“…BP‐Btz more effectively reduced tumour burden and bone loss than Btz in the 5TGM1 mouse model of MM (Wang, Xiao et al, 2018). In particular, we also demonstrated that BP‐Btz generated significantly less systemic adverse effects, such as thrombocytopenia (Wang, Xiao, et al, 2018) and peripheral neuropathy (Wang et al, 2020), compared with Btz alone.…”
Section: Multiple Myelomasupporting
confidence: 54%
“…Although this topic has been covered recently in general reviews (Cole et al, 2016; Farrell et al, 2018; McKenna et al, 2020; Xing et al, 2020), in this article we assess the success of this approach to two areas of bone disease that continue to be unmet medical needs. Specifically, we review work in which bisphosphonates are chemically linked to drugs used clinically to treat multiple myeloma (Wang, Xiao, et al, 2018; Wang et al, 2020) or bone infections (osteomyelitis) (Sedghizadeh, Sun, et al, 2017) that have been used successfully as drug‐releasing conjugates in animal models of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The bone-binding affinity of a BP is predominantly determined by its two geminal phosphonate groups (P-C-P), which form strong bi- and tri-dentate interactions with calcium ions [ 41 , 42 ]. Several different types of bone-targeting drug conjugate candidates have been developed by linking them to BP (e.g., bortezomib [ 43 , 44 ]), and the subject has been extensively reviewed [ 45 , 46 ]. We have sought to create a bone-targeted antibiotic conjugate that could achieve sustained concentrations of drug well above the MBEC at the site of bone infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeted delivery of anti-tumor and anti-vascular therapies using bone and vascular-specific binding motifs are showing promising efficacy in translational studies. Indeed, bone-targeting bortezomib demonstrated improved efficacy in targeting MM as well as reduced side effects compared to conventional bortezomib [51][52][53] . As angiogenesis is a key step in MM progression and interactions between MM and ECs can confer drug resistance, a similar approach in designing and testing bone-targeting anti-angiogenic drugs may be beneficial for MM patients.…”
Section: Discussionmentioning
confidence: 99%